Enhancing strength-ductility synergy in a casting non-equiatomic NiCoCr-based high-entropy alloy by Al and Ti combination addition. (15th July 2021) - Huang, Xueling; Huang, Lanping; Peng, Hailong; Liu, Yong; Liu, Bin; Li, Song
Abstract: A non-equiatomic Ni3.5 Co3 Cr1.5 medium-entropy alloy (AT0) with a single-phase face-centered cubic structure (FCC) directly obtained by arc-melting shows the low yield strength of 147 MPa, ultimate tensile strength of 447 MPa and large total elongation to fracture of 78.8%. By doping Al and Ti, the as-cast (Ni3.5 Co3 Cr1.5 )90 Al5 Ti5 high-entropy alloy (AT5) exhibits enhanced strength-ductility synergy. Compared to AT0 alloy, the yield strength of AT5 alloy increases more than fivefold to 792 MPa, ultimate tensile strength doubles to 1004 MPa, and still remaining a high elongation of 38.2%. The apparent increase in strength can be attributed to uniformly distributed, high-content, conherent (Ni, Co)3 (Al, Ti)-type nanoprecipitates formed in FCC matrix. The formation of various dislocation substructures and crossed stacking faults (SFs) with Lomer-Cottrell locks during tensile deformation is responsible for strain hardening of AT5 alloy. Graphical abstract: Image, graphical abstract